Body counts : medical quantification in historical and sociological perspective - Jorland, Gérard; Weisz, George; Opinel, Annick (Published for Fondation Mérieux by McGill-Queen's University Press = Publié pour Fondation mérieux par McGill-Queen's University Press, 2005)
In an invigorating comparative and interdisciplinary reconsideration of the role of different types of medical counting, this wide-ranging bilingual volume takes us from the mortality tables of the eighteenth century to the movement for evidence-based medicine in our own day. Culled from the proceedings of La quantification dans les sciences médicales et de la santé: perspective historique held at the Musée Claude-Bernard in France in 2002, Body Counts moves beyond the usual emphasis on public health and clinical medicine to include the central role of numbers in laboratory work and medical instrumentation. Body Counts provides an innovative, historical, and sociological account of the functions of quantification.